Pelatihan Penggunaan Geogebra untuk Meningkatkan Pemahaman Matematika Pada Mahasiswa Baru Jurusan Teknik Mesin Unram - Nurchayati, Nurchayati; Hendry Sakke Tira; Yesung Allo Padang; Nurpatria, Nurpatria; Arif Mulyanto (Jurusan Teknik Mesin FT Universitas Mataram, 2025)
Some mathematical objects are abstract. Psychological studies state that children learn concrete things more easily than abstract things. The problem of lack of understanding of mathematical material, especially geometry, both two-dimensional and three-dimensional, also occurs among students. For this reason, the solution offered is training in using Geogebra software to display two- and three-dimensional geometry visually and more realistically. So it can be easier to understand. And this needs to be given to new students as preparation for taking the next lecture at Mechanical Engineering, Mataram University. The implementation of this service is divided into several stages. The first is the preparation of practical instructions for operating Geogebra and questionnaires. Provide tests to measure understanding of basic mathematical concepts, both before and after training. Provide a questionnaire to determine learning motivation before participating in training. Next, provide training on using the Geogebra application/software in solving mathematical problems to participants. Apart from that, participants were also given a questionnaire to find out whether this training was useful for participants and whether this training could motivate participants to learn after attending the training. From the results of observations during the training, the participants were very enthusiastic about taking part, as evidenced by the responses from the participants, both those who asked questions and those who answered the instructor's questions regarding the answers to the questions given. The results of the questionnaire showed that by using Geogebra software it was easier and faster for participants to solve the questions. geometry questions, and there was also an increase in scores before and after training.